An element contribute to customer satisfaction and dissatisfaction towards the new non-billing system provided by Tenaga Nasional Berhad / Faraeza Ismail - Ismail, Faraeza (Faculty of Business and Management, 2003)
TNB has introduced this stabil system as their new technoloqy, which is the new non- billing system. this is the concept of pre-payment meter is designed to gives convenience the consumer to buy an electricity. a smart card pre- payment meter is a metering system with a new billing methodology conventionally the electricity bill is produced after the customer consumes electricity. The philosophy behind is 'pay as you use'. the objectives of this study are determining the "Element that contributes to customer satisfaction and dissatisfaction towards the new non-billing system provided by the TNB".